Monetary policy in a commodity based economy: the case of South Africa - Nesengani, Nkhetheni B., author; Cutler, Harvey, advisor; Braunstein, Elissa, committee member; Jianakoplos, Nancy, committee member; Olienyk, John P., committee member (Colorado State University. Libraries, 2006)
There are many studies done on monetary economics by scholars and central bankers around the world. Most studies cover areas such as inflation, money demand stability, interest rates, credit controls and the effectiveness of different monetary policy approaches. But of these studies, fewer used multi-equation models that included the monetary as well as the real sectors of the economy. A well-specified multi-equation model is the focus of this study when looking at what the monetary authorities in South Africa have been doing. The South African Reserve Bank has over the decades sought of better monetary policy mechanisms to help the Bank, and ultimately the South African economy. Hence, there have been a lot of changes by the Reserve Bank over the years as the monetary authorities responded to changing economic conditions in South Africa and around the world. The South African Reserve Bank was not immune from socio-political issues facing the country. A classic example was how the Bank responded to trade and economic sanctions applied against South Africa by the international countries. South Africa has been a commodity-based economy. For decades it led the world in the production of gold, and it played a major role in the production of other minerals as well. Hence, investments in the mining industry were of great importance. The industry was a backbone for the South African economy. Therefore, it matters that the Reserve Bank should pursue policies that would include encouraging growth in the mining sector. The need for a macroeconomic model that included both the monetary and real sectors of the economy is obvious in a situation where monetary policy variables affect investment, economic growth and consumption. The approach in this study is the use of cointegration in a multi-equations model that includes both the monetary and the real sector of the economy. Real consumption and real investment equations will be the real sector part of the model whereas the monetary sector will be represented by the money demand and money supply equations. The inclusion of the money supply vector in the model brings with it the monetary base variable. This is one of the most important variables in that the monetary authorities have direct control over it. Hence, it becomes an effective policy variable. The biggest single change in ways that the South African Reserve Bank conducted monetary policy was a switch from non-market policy instruments to the use of market oriented policy instruments. So, this study analyses the effectiveness of monetary policy under the two regimes - the non-market and the market approaches. The robustness of the estimated model is analyzed starting from tests for the number of vectors predicted by the theory, the speed of adjustment parameters, correlation coefficients and persistent profiles.
Keywords: finance; models; studies; policy making; South African studies